Supply chain engineering and logistics handbook : inventory and production control - Jones, Erick C. (Boca Raton : CRC Press, an imprint of Taylor & Francis Group, 2019)
"This handbook begins with the history of Supply Chain (SC) Engineering, it goes on to explain how the SC is connected today, and rounds out with future trends. The overall merit of the book is that it introduces a framework similar to sundial that allows an organization to determine where their company may fall on the SC Technology Scale. The book will describe those who are using more historic technologies, companies that are using current collaboration tools for connecting their SC to other global SCs, and the SCs that are moving more towards cutting edge technologies. This book will be a handbook for practitioners, a teaching resource for academics, and a guide for military contractors"--
Introduction to the fourth industrial revolution -- Global supply chain engineering definitions -- Evaluating the impact of sustainability and pipeline quality on the global crude oil supply chain -- Forecasting in global supply chain engineering -- Inventory control -- ERP systems -- Logistics in global supply chain engineering -- Analyzing variability -- How total quality management (TQM) and lean six sigma drove need for supply chain integration -- A relationship between six sigma and Malcom Bridge Quality Award -- Evaluating increasing hospital closure rates in the U.S. -- Total quality management -- The internet of things (IoT) technologies and the tracking of supply chain assets -- Evaluating the impacts of the internet of things to reduce runway incursions -- A methodology to evaluate obsolete inventory in health care -- Manufacturing feasibility evaluation of RFID chips embedded in artificial organs -- Embedding integrated RFID sensors into fiber reinforced plastics during the manufacturing process -- Secure document RFID applications -- Evaluating the impact of sleep disruptions in women through automated analysis -- Evaluating the impact of sustainability incentives to optimize the Indonesian to the United States crude oil supply chain -- Using six sigma to evaluate automatic identification technologies to optimize broken case warehousing operations -- Railroad car tracking by an RFID system to organize traffic flow -- Logistics ecosystems.
OCLC-licensed vendor bibliographic record.
Keywords: Business logistics -- Handbooks, manuals, etc; Inventory control -- Handbooks, manuals, etc